The Yemeni manuscripts of the Yahuda Collection at the University of Michigan - Kropf, Evyn (CEFREPA, 2012)
Introduction The University of Michigan Library is privileged to hold three Yemeni manuscripts in its Islamic Manuscripts Collection, Isl. Ms. 564, Isl. Ms. 589, and Isl. Ms. 638. The manuscripts were identified by cataloguer Evyn Kropf during the “Collaboration in cataloging: Islamic manuscripts at Michigan” project, a grant-funded effort engaging established and emerging scholars by involving them in the detailed cataloguing of the collection. Full codicological descriptions of the manuscripts...